PENERAPAN METODE CONTRAST LIMITED ADAPTIVE HISTOGRAM EQUALIZATION (CLAHE) PADA CITRA DIGITAL UNTUK MEMPERBAIKI GAMBAR X-RAY - Zekson Arizona Matondang (UPPM, 2018)
The Contrast Limited Adaptive Histogram Equalization (CLAHE) method aims to reduce noise bydetermining the kernel matrix and work by replacing the intensity value of each input image pixel with anaverage of the kernel weighting value for each neighboring pixel and pixel itself. In the process of reducingnoise the size of the kernel is very influential in obtaining the results of image quality. The size of the kernelused by the author in this study is 5 x 5.This research has produced an application program to reduce noise using the Contrast Limited AdaptiveHistogram Equalization (CLAHE) method. The test x-ray image used in this study uses x-ray images of thoraxscal. The image is inputted and displayed on the program. Then the Contrast Limited Adaptive HistogramEqualization (CLAHE) process is carried out. Then an image will be produced as desired.